Relationship between capital structure and return on shares: evidence from Latin American markets and the US. - Hansen, Erwin; Torres, Juan Pablo (Estudios de Administración, 2009)
This paper tests whether financial leverage fluctuates in a way which is consistent with the existence of a target leverage or, on the contrary, it freely fluctuates with the observed changes on stock returns. Using a sample of non-financial publicly-traded firms of 5 Latin-American countries and the US in the period 2000-2007, we find that firms allow their leverages fluctuate almost one to one with stock returns variations. This evidence does not mean at all that firms are not involve in corporate debt issuing activity but they do not care too much about hit a particular target.